Pengaruh Disiplin dan Gaya Kepemimpinan Terhadap Kinerja Pegawai Sekretariat DPRD Kabupaten Labuhanbatu - Elvitrianim Purba (Journal of Business and Economics Research (JBE), 2020)
This study aims to determine: (1) the influence of leadership style on the performance of the Labuhanbatu Regency DPRD Secretariat staff (2) the effect of work discipline on the performance of the Labuhanbatu Regency DPRD Secretariat survey research with a quantitative approach. The sample of this study was 150 employees of the Labuhanbatu Regency DPRD Secretariat with population sampling techniques. Data collection used questionnaire while data analysis was carried out using multiple regression analysis. The validity testing in this study uses a technique using the Canfirmatory Factor Analysis (CFA) technique, from the results of the CFA test there are three question items that fall, namely performance question item 6, leadership style 4, and work discipline 6. So out of a total of 22 question items, there are 19 the questions passed the CFA test. At a significant stage 5% of the results of the study found that: (1) leadership style had a positive effect on the performance of the staff of the Secretariat of the Labuhanbatu District Parliament β = 〖0.189〗 ^ * (^ * p <0.005; p = 0.21), with the contribution of the leadership style to employee performance of (〖∆R〗 ^ 2) 0.035. (2) performance discipline has a positive effect on the performance of Labuhanbatu Regency DPRD Secretariat staff β = 〖0.198〗 ^ (*) (^ * p <0.05; p = 0.21), With the contribution of work in stages the employee's performance is 〖(∆R 〗 ^ 2) 0.039. (3) Leadership style and work discipline positively influence the performance of Labuhanbatu Regency DPRD Secretariat staff, which is shown from the results of regression tests that the leadership style β = 〖0.189〗 ^ * (^ * p <0.005; p = 0.021) and work discipline β = 〖0,198〗 ^ (*) (^ * p <0.05; p = 0.21). The contribution of leadership style and work discipline to explain the performance of Labuhanbatu Regency DPRD Secretary employees is (〖∆R〗 ^ 2) 〖0.071〗 ^ *. This means that the ability of leadership style variables and work discipline in explaining variations in performance variables is 7.1%, while the rest is explained by other variables outside the variables studied.